2014
DOI: 10.1063/1.4862806
|View full text |Cite
|
Sign up to set email alerts
|

Tensile strained Ge tunnel field-effect transistors: k · p material modeling and numerical device simulation

Abstract: Group IV based tunnel field-effect transistors generally show lower on-current than III-V based devices because of the weaker phonon-assisted tunneling transitions in the group IV indirect bandgap materials. Direct tunneling in Ge, however, can be enhanced by strain engineering. In this work, we use a 30-band k Á p method to calculate the band structure of biaxial tensile strained Ge and then extract the bandgaps and effective masses at C and L symmetry points in k-space, from which the parameters for the dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…The effect of strain in Ge TFETs has been analyzed in [113] by using quantum-corrected TCAD simulations to estimate the current and · k p calculations for the band parameters. It was found that tensile strain significantly enhances the BTBT rate, similarly to the results for strained Si discussed in section 3.2.…”
Section: Ge-based Tfetsmentioning
confidence: 99%
“…The effect of strain in Ge TFETs has been analyzed in [113] by using quantum-corrected TCAD simulations to estimate the current and · k p calculations for the band parameters. It was found that tensile strain significantly enhances the BTBT rate, similarly to the results for strained Si discussed in section 3.2.…”
Section: Ge-based Tfetsmentioning
confidence: 99%
“…35,36 In relaxed GeSn pTFET, tunneling from the second valence band V2 to Γ conduction band is the dominant component in Fig. 10, it can be seen that G BTBT in tensile strained GeSn pTFET exhibits a higher value than that in relaxed device, which is mainly due to the reduction of direct E G induced by the uniaxial tensile strain.…”
Section: B Gesn Ptfets: Impact Of Uniaxial Tensile Strainmentioning
confidence: 88%
“…9 Enhancing the BTBT rate of direct gap Ge 1−x Sn x alloys is important for high-performance TFETs in application. The direct gap BTBT generation rate G can be described by Kane's model in the form 33,34 …”
Section: Resultsmentioning
confidence: 99%